Análise da ação do tratamento de mobilização neural em pacientes com neuropatia hansênica - CABRAL, André dos Santos (Universidade Federal do Pará, 2017)
Historically Leprosy is one of the most disabling diseases in the world. The symptoms of the disease shows a resultant infectious mixed peripheral neuropathy of an insidious inflammatory process involving an ecological relationship between Mycobacterium leprae and man. Clinical disease turns around, both positive signs such as pain, paresthesia and dysesthesia; as negative signals such as sensorimotor loss and autonomic disturbances. Clinic is similarly developed in patients affected by peripheral compressive neurological syndromes. The neural mobilization has proven an effective manual therapeutic resource in controlling the symptoms of these compression syndromes. The inflammatory nature of leprosy neuropathy perform a compressive action and limiting of the mobility of peripheral nerve, impacting negatively with part of the pathology of the disease. This work aimed to investigate the neural mobilization technique is able to improve the symptoms of leprosy neuropathy. Therefore developed a clinical study, longitudinal, non-randomized, self-control, with an experimental analysis of quantitative character, consisting of four different moments, evaluation, experimental intervention period and revaluation 1 and 2. Were examined 12 upper limbs of six patients with high poliquimioterapêutico scheme for multibacillary for clinical form Borderline, who had neurological neurological impairment and remaining neural symptoms. A total of 23 nerve trunks still were symptomatic during the evaluation, taking an average of 3.8 ± 1.8 per patient nerve trunks. Most incidents symptoms to palpation assessment were paresthesia (20) and pain (09). The average intensity of neuropathic pain of each MS was 6.33±3.24. It still has measured grip strength and the sensitivity of the palm side for comparison after the intervention. After 12 sessions of neural mobilization upper limbs there was a slight improvement of sensitivity and grip strength but it was not significant. At the end of the experimental treatment, the number of symptomatic nerve trunks of upper limb decreased significantly. It was also observed analgesia of all upper limbs treated, with maintenance of this benefit after a post-expiration month of the intervention period. With these results we can conclude that the treatment of neural mobilization proved to be effective in controlling leprosy neuropathic pain.